Energy Policy in Perspective : Today's Problems, Yesterday's Solutions - Goodwin, Craufurd D. W. (Washington, D.C.: Brookings Institution, 1981)
This present study examines the formulation of energy policy from the end of World War 2 through 1979. The study is intended to enable the reader to judge the nation's present energy problems and the policies advocated for their solution in historical perspective.
Includes index: p. 707-728.
Bibliographical references.
ne 5/04/2018
Loans
Keywords: Energy Policy